EXAMINING SERVANT LEADERSHIP IN EFFECTIVE SCHOOL GOVERNANCE - Nienaber, Hester (International Journal of Educational Development in Africa, 2014)
The issue of effective school governance ensuring quality in education in South Africa is often raised in the literature. Some authors are of the view that the current form of school governance is sophisticated and complex. A question that arises is whether school governing board members have the skills to effectively discharge their responsibility. Literature suggests training as a means of capacitating members to be able to effectively do so. However, limited success is achieved with training. The question thus arises whether the training is perhaps too limited. Servant leadership is examined as an alternative to empower members of school governing bodies to effectively discharge responsibilities. According to servant leadership, all members of a group/community, irrespective of designation, can contribute to the betterment of the group/community.